Factors Influencing on Poverty in the View of Married Women with Higher Education Degree - MOHAMMAD ABBASZADEH; leyla nasrolahi vosta (توسعه اجتماعی)
Current study aims to meaning discovery of poverty phenomenon in the society. Core questions of this research are: what factors lead to poverty in the view of married students of Tehran University? What strategies can be provided to remove poverty phenomenon? And what are the consequences of poverty in their view? Current study is based on grounded theory. Sampling was purposefull-hudgemental method from female married students in married dormitories of Tehran University. Results indicated that “employment in non-specialized”, “lack of income”, “unemployment by governmental organizations”, “lack of certain policies for employment of educated people through country officials”, “high living costs”, “lack of job opportunities for educated people”, and “existing rent in governmental organizations in the process of employment” were the most important determinants of poverty phenomenon. The causes were economic and managerial (governance) factors. Gender inequality and negative attitude towards women’ work in the society that is originated from historical background of the country, are key contextual and mediating factors affecting poverty phenomenon.